Utilização da farinha de couro na alimentação de frango de corte - Pinheiro, João Waine; Mizubuti, Ivone Yurika; Rocha, Marco Antonio da; Reddy, Kuruganti Venkatakrisnha (Semina: Ciências Agrárias, 1989)
<!--[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> A study was conducted using 128 hubbard chickens sexed at 3 days age to verify the possibility of utilizing unhidrolyzed leather meal (U.L.M.) in the feed. The broiler chicks were distributed according to a 4 x 2 factorial design in randomized blocks (treatment and sex) and with two replications and eight birds for experimental unit. The duration of the experiment was 4 weeks and the chicks were housed in metallic cages with electric light hearing. The feed diets were formulated with 0; 3; 6, or 9% of U.L.M. and had 21,2% CP. The results on feed consumption, average weight gain and feed conversion were: 1.43kg, 0.914kg and 1.56kg; 1.48kg, 0,938kg and 1.58kg; 1.44kg, 0.887kg and 1.62kg; 1.35kg, 0.807kg and 1.67kg for 0; 3; 6 e 9% U.L.M. contained rations respectively. The analysis of variance showed that 1) there was no significant effect between treatments (P > 0,05) on feed consumption. 2) the maximum weight gain was obtained wit 2.59% of U.L.M. 3) The birds fed diets with 3% and 6% U.L.M. demonstrated weight gain and feed conversion similar to those fed zero % U.L.M. ration (P > 0.05). The results in this study concluded that the adition of 6% U.L.M. in diets of broiler chicken did not significantly effect the chicken performance at 28 days of the experiment.